2020
DOI: 10.1038/s41467-020-19799-2
|View full text |Cite
|
Sign up to set email alerts
|

Universal light-guiding geometry for on-chip resonators having extremely high Q-factor

Abstract: By providing an effective way to leverage nonlinear phenomena in integrated devices, high-Q optical resonators have led to recent advances in on-chip photonics. However, developing fabrication processes to shape any new material into a resonator with extremely smooth surfaces on a chip has been an exceptionally challenging task. Here, we describe a universal method to implement ultra-high-Q resonators with any new material having desirable properties that can be deposited by physical vapor deposition. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…hydrogen impurities. While the hydrogen absorption loss can be efficiently eliminated via repeated thermal annealing of Si 3 N 4 at high temperature (~1200 ∘ C) 26 , 68 , efforts on loss reduction have mainly been focused on reducing waveguide roughness via optimized dry etching 25 and etchless processes 76 , 77 . In addition, the large mode area of thin-core Si 3 N 4 waveguides 49 51 results in reduced optical mode interaction with waveguide sidewall roughness, and thereby reduced scattering losses.…”
Section: Resultsmentioning
confidence: 99%
“…hydrogen impurities. While the hydrogen absorption loss can be efficiently eliminated via repeated thermal annealing of Si 3 N 4 at high temperature (~1200 ∘ C) 26 , 68 , efforts on loss reduction have mainly been focused on reducing waveguide roughness via optimized dry etching 25 and etchless processes 76 , 77 . In addition, the large mode area of thin-core Si 3 N 4 waveguides 49 51 results in reduced optical mode interaction with waveguide sidewall roughness, and thereby reduced scattering losses.…”
Section: Resultsmentioning
confidence: 99%
“…The diameter of the MRR and the thickness of the deposited layer were set to 4.94 mm and 1.3 µm, respectively. They put forward a flip‐chip coupling scheme in which the coupling waveguide is flipped over and coupled with the resonator 92 …”
Section: Chalcogenide Glass Microringsmentioning
confidence: 99%
“…They put forward a flip-chip coupling scheme in which the coupling waveguide is flipped over and coupled with the resonator. 92 Du et al investigated low-loss MRR fabrication in Ge 23 Sb 7 S 70 glass composition. 93 Later, Shen et al reported for the first time the reconfigurable control of resonance splitting in Ge 23 Sb 7 S 70 MRR by writing Bragg gratings using the cavity-enhanced photosensitivity of MRR at 1.55 µm using high power >150 mW inside the MRR with <10 mW waveguide power.…”
Section: Chalcogenide Glass Microringsmentioning
confidence: 99%
“…The material is Ge25Sb10S65 (GeSbS) that inherits the ultrabroad transmission window with absence of TPA, large refractive index and Kerr nonlinearity [37][38][39][40][41][42] of ChGs, and shows flexibility in photonic integration on silicon-based chips [43][44][45] . In the meantime, with modified compounds, GeSbS could overcome existing problems of As-based ChGs, and features an improved laser damage threshold (LDT) with a reduced TOC.…”
Section: Introductionmentioning
confidence: 99%